Computational study of transmission function in p-phenylene sulfide and benzothiophene oligomers - Yuthana Tantirungrotechai (2018)
The transmission function T(E), which describes the conduction in molecule, and the density of state (DOS) of the helical p-phenylene sulfide oligomer and of the fused-planar benzothiophene oligomer were calculated by using the non-equilibrium Green's function formalism. Although both the oligomers consist of benzene-(1,4)-dithiolate subunit, they have different T(E) and DOS near the Fermi level. The effect of replacing a sulfur atom inside the oligomer by an oxygen atom was additionally investigated.